2019
DOI: 10.3390/cells8121638
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs in IGF-1R Signaling Regulation: The Underlying Pathophysiological Link between Diabetes and Cancer

Abstract: The intricate molecular network shared between diabetes mellitus (DM) and cancer has been broadly understood. DM has been associated with several hormone-dependent malignancies, including breast, pancreatic, and colorectal cancer (CRC). Insulin resistance, hyperglycemia, and inflammation are the main pathophysiological mechanisms linking DM to cancer. Non-coding RNAs (ncRNAs), particularly microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), are widely appreciated as pervasive regulators of gene expression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 117 publications
2
35
0
Order By: Relevance
“…Among those, the best characterized factors include microRNAs (miRNAs) and long non-coding RNAs (lncRNAs). As nicely previously reviewed [ 94 , 95 ], a large variety of miRNAs and lncRNAs regulate the IGF axis in tumor cells with functional implications in various stages of tumor malignancy. In addition, complex interactions among miRNAs and lncRNAs might also regulate various members of the IGF axis.…”
Section: Novel Regulators Of the Igf System And Their Impact In Camentioning
confidence: 98%
“…Among those, the best characterized factors include microRNAs (miRNAs) and long non-coding RNAs (lncRNAs). As nicely previously reviewed [ 94 , 95 ], a large variety of miRNAs and lncRNAs regulate the IGF axis in tumor cells with functional implications in various stages of tumor malignancy. In addition, complex interactions among miRNAs and lncRNAs might also regulate various members of the IGF axis.…”
Section: Novel Regulators Of the Igf System And Their Impact In Camentioning
confidence: 98%
“…12 Indeed, a number of noncoding RNAs have been identified that regulate the insulin growth factor-1 receptor (IGF-1R), a master regulator in DM and cancer. 37 Although observational trials have demonstrated that DM is associated with major subtypes of dementia, in particular dementias with obvious vascular pathologies (eg, vascular dementia and unspecified dementia), MR has not shown T2DM to be a direct cause of AD in a recent two-sample study. 38 The MR approach has not been viable to date to test the causal effect between T2DM and vascular and unspecified dementia due to the lack of publicly available genetic data.…”
Section: Linking Conditions Of the Diabetes Syndrome Through Genes Anmentioning
confidence: 96%
“…In particular, adipose tissue dysfunction plays an important role by inducing insulin resistance, chronic inflammation, and changes in adipokines serum levels (including leptin and adiponectin), as well as sex steroids, and thereby promoting cell proliferation and survival, as well as invasive growth, metastasis, and angiogenesis [32,33]. In more recent years, a direct association between the development of diabetes and several different cancers (i.e., pancreas, breast, endometrium, colorectal [33][34][35], cutaneous and uveal melanoma [36]) has been demonstrated. Alterations in insulin and insulin-like growth factor type 1 (IGF-1) signalling pathways have been identified as the main drivers that lead to the development of both diabetes and cancer.…”
Section: Metabolic Syndrome Cancer and Cardiovascular Diseasesmentioning
confidence: 99%
“…Alterations in insulin and insulin-like growth factor type 1 (IGF-1) signalling pathways have been identified as the main drivers that lead to the development of both diabetes and cancer. From a pathophysiological standpoint, in the regulation of the carcinogenic process in patients with diabetes, specific alterations in both microRNAs and long non-coding RNAs affecting insulin signalling have been described [33]. In the Vasterbotten intervention project, it was clearly shown that, in women, the risk of developing cancer was higher in subjects with elevated fasting glucose level, and in both sexes, there was a significant increase in pancreatic, endometrial and urinary tract cancer, as well as melanoma [37].…”
Section: Metabolic Syndrome Cancer and Cardiovascular Diseasesmentioning
confidence: 99%